Rain Tourism: A Progressive Opportunity and Challenges for Konkan Tourism - Dr. Deepali Garge, Mr. Sandeep Narayan Naik, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Konkan region is located in Maharashtra state surrounded by Sahyadri hills ranges in the west, metro city Mumbai and suburbs in the north, Goa in the south and mighty Arabian Sea in the east. It enjoys 720 km long coastline, it is one of the unexploited tourism destination in India which has a huge potential to attract and provide a mesmerising service to the tourists. Konkan is blessed with surprisingly natural waterfalls amid green canopy mountains and beautiful popping out Wadis welcoming the tourists with a wonderful gesture of delicious mouth-watering signature delicacies, rich culture and down to earth ethnic hospitality. The waving coconut trees directing the visitors towards the gorgeous emerald virgin beaches, historical forts, ancient temples, mango and beetle nut grooves. It bears all the pre-requisites that perfectly fit into various types of tourism formats like religious tourism, cultural tourism, ethnic tourism, rural tourism, agro tourism, Senior citizen tourism, Adventure tourism, Food tourism, etc. But unfortunately due to heavy rainfall during rainy season it experiences a rock bottom low in terms of tourist flow. Rainy season in Konkan persists from the month of June to the month of September. It has measured more than 4000 mm rainfall at an average last year that is almost 57% above normal rainfall in Maharashtra. Many of the time it observes flood situations. The rainfall trends experienced usually by Konkan region states that June and July are aggressive month with heavy rainfall followed by reduced intensity of rain from August to October. Thus June and July can be focused on adventurous and risk taker topological tourists while August, September and October can be focused on senior citizen and family oriented tourists. The researcher tries to identify a niche kind of tourism opportunity that is rain tourism which will focus on attracting tourists’ inflow during the slack period from various locations of Maharashtra, India and across the globe that have below average or low rainfall at their place. A detailed SWOC analysis of Konkan is done to highlight the challenges and opportunities so it can arise as sustainable and a notable contender in achieving 5 trillion economy of India. Konkan can possibly generate lot of opportunities during rainy season to attract domestic and international tourist around the World at a large who have below average or low rainfall during rainy season. Konkan can provide them with a memory to cherish for a lifetime with beautiful jade scenic beauty, aroma of freshness, crabs and frogs moving around with mouth-watering hot snacks and local delicacies. In addition to this it can have value added infrastructure for rain based activities like Mud pies for rain dance, Rain gears loaded heritage walk, Monsoon camping, Rain gauge workshop, Rice farms plantation activity, Ayurveda spa, Rain trek, Horse safari, natural waterfall showers, Open discotheque, Wine and beer appreciation and testing sessions, Government or NGO initiated Food tourism events like Rain food festivals or cookery shows etc., Rain sports like football, volley ball etc., adventure sports like river rafting, Waterfall rappelling and many more. If this opportunity will be converted in to reality will help, the temporary hospitality workforce that is laid-off due to off-season to have hopes of being financially benefitted with job security, locals will have direct and indirect source of income. Due to revenue generation by the government through taxes it will concentrate on developing a safe infrastructure for Konkan region with respect to rainy season. If the above stated opportunities be converted in to reality it will gradually add on to the nations GDP for sure. Konkan has to firstly be optimistic about the concept of rain tourism as history has revealed that rain has always come up with disaster and loss. With the government intervention by developing proper roadways, railway network and proper whether forecast and alerts the situation is getting better. Konkan faces many challenges in many aspects to get this niche tourism concept into reality starting from changing the mind-set of locals favouring this innovative enterprise and gaining their support along with skill development and expertise. Accessibility infrastructure which will be safe and secured like good quality and big roads, specially trained drivers etc. Medical infrastructure including good medical assistance and quick response team. Digital infrastructure like Wi-Fi, mobile network, high speed internet has become the basic necessity presently hence it is required to be developed at least at the tourist destinations. Power failure especially during rainy seasons is a normal, the government needs to find out solution to curb this issue and ensure 24hrs electricity or backups by the hoteliers. Aggressive marketing using digital marketing tools and travel agents networking is very essential to make this seed idea to flourish in a success story. Advertisement will help to create awareness, develop confidence and motivate the potential tourists to opt for it. Government or NGO should initiate with an emergency rescue task support team who can rush in case of any unforeseen calamities. The safety and security concerns need to be properly dealt by the Police department with more check post to control immoral and illegal practices that might occur during rainy season. The researcher has not only explored the potential opportunities and possible challenges during rainy season in Konkan but also has tried to analyse the perception, willingness and acceptance by the probable tourists with the help of well-developed questionnaire through digital survey tools like Google forms etc. The hypothesis made by the researcher has been statistically tested to prove the significance of the concept. Rain tourism concept is an innovative niche avenue that can be applied to all other tourism destinations with heavy rainfall and slack business during that period. With lot of opportunities in the concept, if the challenges faced are dealt in a professional and planned way will give rise to a new transformation. Rain tourism has a great prospective to streamline the economic graph of the destination which goes down during the rainy season and raise it upwards.